Review on Selected Toxic, Narcotics and Psychoactive Plants Used in Nigeria - Isyaka, Sani M.; Salisu, Ibrahim; Abdullahi, Abdullahi M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2025)
One in seven Nigerians aged 15 to 64 had used illicit substances (other than tobacco and alcohol) in the past year, with significant numbers suffering from drug-related disorders. Cannabis, known as marijuana or Indian hemp, contains THC, which affects brain receptors. Short-term effects include mood swings, memory loss, and poor coordination, while regular use can lead to anxiety, depression, and respiratory problems. Nigeria has strict laws against cannabis use, with severe penalties for possession and distribution. Tobacco is widely used for its nicotine content. Short-term effects include high blood pressure and increased heart rate, while long-term use can lead to lung cancer and heart disease. Smoking is legal in Nigeria, but there are efforts to reduce tobacco usage through taxes and health campaigns. Khat, or miraa, contains cathinone, causing similar short-term effects as tobacco. Though illegal in Nigeria, it remains used in some Northern communities. Datura stramonium, or jimsonweed, contains harmful substances that can cause hallucinations. Its use is also illegal in Nigeria, its traditional medicine practices can be risky despite potential benefits. The purpose of this review is to develop a review of current research on toxic, narcotic, psychoactive plants and ecological risk assessment, as well as to point out deficiencies and to offer motivation for enhancing the research level in this field. Research on psychoactive plants is being conducted progressively, and significant progress has been made in the aspects of occurrence. Nevertheless, there are some areas for improvement and more research needs be carried on the selected plants as well as other plants in existence.